PENGARUH STRATEGI BAURAN PEMASARAN TERHADAP NIAT PEMBELIAN ULANG PRODUK SEPEDA MOTOR - Budiyanto Budiyanto; Didit Darmawan (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2005)
The objective of this research is to examine the effect of the marketing mix strategy on repeat purchase. Based on litelature review, it was hypothesized that marketing mix strategy has a significant effect on repeat purchase. Using questionnaire, this research have collected data from 100 partisipants inSurabaya. Regression linear analysis was used to test hypothesis. The results show that two elements of marketing mix; product and price, have significant effect on repeat purchase.